PENGEMBANGAN MEDIA PETUALANGAN MATEMATIKA (PETAMATIKA) PADA MATERI KELILING DAN LUAS BANGUN DATAR UNTUK KELAS IV SEKOLAH DASAR - Dini Fitria Sari Karnen; Meita Fitrianawati (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2022)
This study aims to determine the development procedures and determine the feasibility of the Petulangan Matematika (Petamatika) media.. This research is a type of Research and Development (R&D) used the Borg and Gall development model with the following stages: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revisions, (6) main field testing (small-scale), (7) operational product revisions and (8) operational field testing (large-scale). The trial subjects used were 27 students in IV grade and teachers in Muhammadiyah Tamantirto Elementary School. Data collection techniques in the form of interviews, observation and questionnaires. Data analysis includes quantitative data analysis and qualitative data analysis. The results showed that the validation of the media experts scored 78.33 in the "Good" category, the validation of the material experts scored 81.67 with the "Very Good" category and the validation of the learning expert scored 90 with the "Very Good" category. The results of small-scale field trials get a value of 87.16 with the category "Very Good" and the results of large-scale trials get a value of 94.91 with the category "Very Good". From all assessments of experts, students and teachers, the Petulangan Matematika (Petamatika) media scored an average score of 86.41 in the "Very Good" category and was declared eligible for use in the material of perimeter and areas of two dimensional shapes for grade IV elementary schools.